2017
DOI: 10.1007/s11427-017-9199-1
|View full text |Cite
|
Sign up to set email alerts
|

An expression atlas of miRNAs in Arabidopsis thaliana

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate a variety of biological processes. MiRNA expression often exhibits spatial and temporal specificity. However, genome-wide miRNA expression patterns in different organs during development of Arabidopsis thaliana have not yet been systemically investigated. In this study, we sequenced small RNA libraries generated from 27 different organ/tissue types, which cover the entire life cycle of Arabidopsis. Analysis of the sequencing data revealed that most miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 90 publications
(126 reference statements)
0
34
0
Order By: Relevance
“…Twelve miRNA families had relatively high levels during early embryogenesis and decreased thereafter. Based on further analysis of internally generated and publicly available sRNA-seq data from 26 tissue-types (Xu et al, 2018) , five miRNA families were highly enriched during the initial stages of embryogenesis including miR156b-3p, miR831, miR845, miR866-3p and miR3440b-3p ( Figures 3B and S2). To examine whether miRNA levels vary between early embryonic cell-types, we adapted a sRNA in situ protocol (Ghosh Dastidar et al, 2016) to detect four selected miRNAs in early embryos.…”
Section: Embryonic Mirna Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve miRNA families had relatively high levels during early embryogenesis and decreased thereafter. Based on further analysis of internally generated and publicly available sRNA-seq data from 26 tissue-types (Xu et al, 2018) , five miRNA families were highly enriched during the initial stages of embryogenesis including miR156b-3p, miR831, miR845, miR866-3p and miR3440b-3p ( Figures 3B and S2). To examine whether miRNA levels vary between early embryonic cell-types, we adapted a sRNA in situ protocol (Ghosh Dastidar et al, 2016) to detect four selected miRNAs in early embryos.…”
Section: Embryonic Mirna Dynamicsmentioning
confidence: 99%
“…Five miRNA families were selected based on their enrichment in embryos compared to internally generated leaf and floral bud sRNA-seq libraries. sRNA-seq libraries generated internally are marked in bold and published sRNA-seq data from 26 tissue types (Xu et al, 2018) are also shown. (C) Representative images of miRNA in situ hybridizations on sections of embryos.…”
Section: Embryonic Mirna Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, miRNA expression profiling studies of multiple tumor types have revealed that aberrantly expressed miRNAs are beneficial for the classification, diagnosis, staging, and prognosis of disease [15]. The analysis of sequencing data from 27 different organs/tissues of Arabidopsis also proved that most miRNAs are widely expressed, whereas a fraction of miRNAs exhibit tissue-specific expression patterns [16].…”
Section: Tissue and Temporal Specificitymentioning
confidence: 99%
“…Juvenile plants exhibit a high cytokinin response and regenerative capacity. As a plant ages, miR156 levels decline, alleviating the repression of its SPL targets (Wang et al, 2009;Yamaguchi et al, 2009;Xu et al, 2018). SPL directly inhibits the transcriptional activity of B-type ARABIDOPSIS RESPONSE REGULATORs and thereby impairs shoot regenerative capacity (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%